The Influence of Transparency, Accountability, and Responsiveness on Public Trust in Padang Command Center 112 Services - Amalia, Disa; Frinaldi, Aldri; Naldi, Hendra; Magriasti, Lince (Journal of Economics and Management Scienties, 2025)
This study examines the influence of transparency, accountability, and responsiveness on public trust in the Padang Command Center 112 (PCC 112) as a model of digital governance in local government service systems. The research aims to identify the most dominant governance dimension affecting public confidence and to evaluate the interrelationship among the three key variables within the framework of good governance. The study employed a quantitative approach using a structured survey of 166 respondents, analyzed through descriptive statistics, Pearson correlation, and multiple linear regression. The findings reveal that all three variables have a strong and significant relationship with public trust, with transparency emerging as the most influential predictor (β = 0.530), followed by responsiveness (β = 0.251) and accountability (β = 0.107). The regression model yielded an Adjusted R² of 0.705, indicating that these governance dimensions jointly explain 70.5% of the variance in public trust. The results confirm that transparent information, timely response, and ethical responsibility are essential determinants of citizen confidence in digital public services. This study contributes to the literature on governance-based trust formation and provides strategic insights for enhancing institutional legitimacy through ethical and participatory digital governance.